2019
DOI: 10.1155/2019/8621486
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Treated Wood as a Substrate for Coatings, Weathering of Heat-Treated Wood, and Coating Performance on Heat-Treated Wood

Abstract: Heat treatment is a method of wood modification with increasing market acceptance in Europe. The major patented European commercial heat treatment processes have trade names ThermoWood, Platowood, Retiwood, Le Bois Perdure, and Oil-Heat-Treated Wood (OHT). To what extent modification of wood affects the resistance of wood to weathering is also an important aspect for wood applications, especially where appearance is important. Unfortunately, heat-treated wood has poor resistance to weathering, and surface trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Although wood is substantially transformed during thermal modification, in a number of studies, it has been observed that the coating formulations intended for the use on unmodified wood suits as well for application on TM wood as a substrate [26][27][28]. Nonetheless, the increased hydrophobic character of heat-treated wood and the changes of the polarity of surface energy of wood could cause problems with the adhesion of waterborne coatings [29].…”
Section: Introductionmentioning
confidence: 99%
“…Although wood is substantially transformed during thermal modification, in a number of studies, it has been observed that the coating formulations intended for the use on unmodified wood suits as well for application on TM wood as a substrate [26][27][28]. Nonetheless, the increased hydrophobic character of heat-treated wood and the changes of the polarity of surface energy of wood could cause problems with the adhesion of waterborne coatings [29].…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with findings that vegetable oils do not penetrate cell walls [17], making it possible to apply a coat of paint. However, it is not recommended to use wood after modification without any coating for outdoor use, as it is not weather-resistant [18].…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that thermally modified wood has poor resistance against weathering, and surface treatment with coatings is required for both protection and aesthetic reasons. A more detailed review of the recent results in the field of weathering performance of thermally modified wood is given in the paper prepared by Jirouš-Rajković and Miklečić [ 207 ].…”
Section: Thermal Modificationmentioning
confidence: 99%